Interpersonal Communication of Persons with Visual Impairments: Its Influence on Self-Concept and Resilience among Members of the Indonesian Blind Association Community in Medan City, Indonesia - Nurhayati Nurhayati; Iskandar Zulkarnain; Humaizi Humaizi (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2026)
Loss of vision after birth requires individuals to make psychological and social adjustments so that interpersonal communication becomes a factor that has the potential to support the formation of self-concept and resilience. This study aims to analyze the influence of interpersonal communication on the self-concept and resilience of people with non-congenital visual impairments among members of the Indonesian Blind Association (PERTUNI) in Medan City. The study used a quantitative approach with a correlational method. The study population was 120 members of PERTUNI in Medan City and all of them were sampled through a total sampling technique. Data were collected using a questionnaire that was read directly to respondents and analyzed using SPSS version 27. The results showed that interpersonal communication had a positive and significant effect on self-concept (β = 0.210; t = 2.936; p = 0.004) with a coefficient of determination of 0.068, which means it explains 6.8% of the variation in self-concept. Interpersonal communication also had a positive and significant effect on resilience (β = 0.384; t = 3.829; p = 0.001) with a coefficient of determination of 0.111 or explaining 11.1% of the variation in resilience. This finding indicates that interpersonal communication contributes to the formation of self-concept and resilience in people with non-congenital visual impairments.